The effect of feed production technology on pellet durability - Borovik Evgeny S.; Menyakina Anna G.; Gamko Leonid N.; Podolnikov Valery E.; Sidorov Ivan I. (BIO Web of Conferences)
The physical parameters of the feed pellet are most influenced by the technology of feed production. The main stages of production are grinding, conditioning, granulation, and cooling. During the crushing process, it is necessary to strive for a homogeneous fine fraction of the feed mixture. Conditioning provides mechanical, thermal, and chemical feed preparation. Special attention should be paid to the steaming time (exposure), steam quality, and moisture content of the feed mixture, which ultimately affects the durability of pellets. The durability of the granules depends on all stages of production, down to cooling. The feed components and their quantity are important for granulation because they have different pelletability. To achieve the best durability of the pellets, they require accounting and adjustment, nevertheless, the effect of the diet composition on the quality of pellets does not exceed 25%, according to the researchers. Changing formulations to improve the quality of pellets is considered as a last resort, since it is associated with high costs, it is always cheaper to reconfigure and modernize equipment to achieve the quantity and quality of pellet feed. The pellet quality coefficients can serve as a preliminary assessment of the future pellet, help to anticipate any problems before the start of feed production. Pellet quality control at the feed mill and growing sites is necessary to identify and make adjustments in a timely manner to maintain stable pellet quality.